THE TESTING IN THE PREPEARING OF THE FUTURE SOCIAL WORKERS - Котикова, О. М. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
The state devotes for clarifying the relation of traditional and i The author analyzes the various advantages and disadvantages of test control, the problem of drawing up of didactic tests for specialists of social sphere, highlights the experience of test technologies in the training of future social workers. The author analyzes the various advantages and disadvantages of test control, the problem of drawing up of didactic tests for specialists of social sphere, highlights the experience of test technologies in the training of future social workers. The data provide an opportunity to the organization of combined control methods in the training of future social workers